Using conductive fabrics as inflation sensors for pneumatic artificial muscles. (18th August 2021) - Hitzmann, Arne; Wang, Yanlin; Kessler, Tyler; Hosoda, Koh
Abstract : Utilizing McKibben pneumatic artificial muscles is a widely accepted method to achieve compliance in applications where adaptability is desirable. Controlling their lengths in an open-loop based on pressure is still challenging, due to their non-linear nature, even more so if external perturbations can occur. Generating inflation or length feedback was, therefore, the goal of several previous sensor designs. However, preserving the actuator's flexibility and lightweight characteristics was not a typical consideration for those designs. This paper will describe our design of an inflation sensor made from conductive fabrics. Our design's minimalistic approach resulted in an easy-to-manufacture sensor that does not alter the actuator's shape or flexibility that also can be individually replaced. This design allows the sensor to be deployed into complex muscular systems, where rigid sensors potentially interfere with adjacent actuators. In this paper, we will describe the production of our sensor, its static response, and its dynamic response under load. The results of our experiments confirmed the viability of the usage of conductive fabrics for this type of sensor while conserving the desirable properties of McKibben pneumatic artificial muscles. GRAPHICAL ABSTRACT: UF0001